ANALISIS STRATEGI PEMASARAN PRODUK KULINER KHAS KOREA SELATAN (Studi Kasus pada OMO Korean Street Food) - Ida Ayu Putu Megawati (JURNAL LENTERA BISNIS, 2023)
The behavior patterns of society that are experiencing a transition during the COVID-19 pandemic have increased the influence of the Korean Wave in Indonesia. The momentum of the Korean Wave in Indonesia provides opportunities for the rise of small and medium-sized enterprises (MSMEs) in Indonesia, especially in the culinary field. OMO Korean Street Food is one of the MSMEs that is taking advantage of this opportunity. This research discusses the reasons and strategies used by the owner of the Korean culinary snack business. The research method used is a qualitative research method. The data collection techniques used are in-depth interviews and documentation. By using a marketing mix strategy and SWOT analysis, OMO Korean Street Food can overcome weaknesses with strengths and anticipate threats with opportunities.Keywords: MSME, Strategy, Marketing, Marketing Mix, SWOT Analysis